THEORETICAL AND PRACTICAL FOUNDATIONS OF DEVELOPING PHYSICAL WORK CAPACITY IN THE PROCESS OF PHYSICAL TRAINING OF YOUNG JUDO ATHLETES (SCIENCE TIME JOURNAL, 2026)
The general objective of the study was the scientific defense and experimental confirmation of the efficacy of a structured 6-month training program, which is specifically aimed at the promotion of physical working capacity in the 10-12 year old judo athletes. The study aimed at evaluating the claim that a systematically structured array of general and special physical training programs wouldproduce meaningful changes on the functional and performance parameters of young judokas at a pivotal point in their sporting career.Twenty young judo players aged 10-12 years were part and parcel of the experimental study. The training intervention was implemented within 6 months, and the sessions took every three weeks based on the structured training program. The program was based on the balanced approach of inclusion of general physical preparation (GPP) and special physical preparation (SPP),with appropriate distribution of loads depending on age. Means of training comprised aerobic and anaerobic conditioning exercises, strength and coordination exercises, and sport-specific exercises based on judo performance. The circuit training method and the interval training method were applied systematically to enhance endurance, muscular strength and functional stability. The parameters of the load were gradually raised according to the principles of gradual overload and adaptation. In order to assess the efficacy of the program, the following tests were carried out in the pre and post intervention period: